EP428 Risk of involvement of sentinel lymph nodes in cervical cancer stage IA1 with lymphovascular space invasion and and IA2. (1st November 2019) - Vetrovska, M; Pichlik, T; Rob, L; Robova, H; Halaska, M; Drozenova, J; Hruda, M; Drochytek, V
Abstract : Introduction/Background: To evaluate the risk of involvement of sentinel lymph nodes in cervical cancer stage IA1 with lymphovascular space invasion (LVSI) and IA2 using the detection of sentinel lymph nodes and histopathology ultramicrostaging. Methodology: The study included women from prospective protocols LAP I and LAP II with cervical cancer squamous or adenocarcinoma stage IA1 with LVSI and stage IA2 from 2002 to 2018 classified according to FIGO 2014 staging, TNM 8. Detection of sentinel lymph nodes throughout this period was performed by using ultra-short protocol with Tc and patent blue and histopathology evaluation by ultramicrostaging histopathological protocol. Results: In the first group (28 women) with stage IA1 and lymphovascular space invasion diagnosed from cone biopsy (all LVSI cases was confirm by expert oncogynecology pathologist). There were 2 women with positive lymph nodes (7, 1%). In the group stage IA2 (34 women) there were 13 women (38, 2%) with positive lymphovascular space invasion and 2 women had positive lymph nodes (5, 9%). The risk of positive lymph nodes for stage IA1 with lymphovascular space invasion and for stage IA2 is not statistically significant OR=0.8125 (95% CI: 0.1070–6.172). Conclusion: The detection of sentinel lymph nodes aids to individualize the therapy of early stage cervical cancer and helps to reduce the radicalisation of surgery. The risk of positive lymph nodes in stage IA1 with lymphovascular space invasion and stage IA2 with/without lymphovascular space invasion is the same. The results confirm, that the detection of sentinel lymph nodes in stage IA1 with lymphovascular space invasion is fully indicated. It would be interesting to compare these results with new FIGO classification. Disclosure: Nothing to disclose.